Exploring the RNA Gap for Improving Diagnostic Yield in Primary Immunodeficiencies - Lye, Jed J.; Williams, Anthony; Baralle, Diana (Frontiers in Genetics, 2019)
Challenges in diagnosing primary immunodeficiency are numerous and diverse, with current whole-exome and whole-genome sequencing approaches only able to reach a molecular diagnosis in 25–60% of cases. We assess these problems and discuss how RNA-focused analysis has expanded and improved in recent years and may now be utilized to gain an unparalleled insight into cellular immunology. We review how investigation into RNA biology can give information regarding the differential expression, monoallelic expression, and alternative splicing—which have important roles in immune regulation and function. We show how this information can inform bioinformatic analysis pipelines and aid in the variant filtering process, expediting the identification of causal variants—especially those affecting splicing—and enhance overall diagnostic ability. We also demonstrate the challenges, which remain in the design of this type of investigation, regarding technological limitation and biological considerations and suggest potential directions for the clinical applications.